Computational Analysis of AmpSeq Data for Targeted, High-Throughput Genotyping of Amplicons - Fresnedo-Ramírez, Jonathan; Yang, Shanshan; Sun, Qi; Karn, Avinash; Reisch, Bruce I.; Cadle-Davidson, Lance (Frontiers in Plant Science, 2019)
Amplicon sequencing (AmpSeq) is a practical, intuitive strategy with a semi-automated computational pipeline for analysis of highly multiplexed PCR-derived sequences. This genotyping platform is particularly cost-effective when multiplexing 96 or more samples with a few amplicons up to thousands of amplicons. Amplicons can target from a single nucleotide to the upper limit of the sequencing platform. The flexibility of AmpSeq’s wet lab methods make it a tool of broad interest for diverse species, and AmpSeq excels in flexibility, high-throughput, low-cost, accuracy, and semi-automated analysis. Here we provide an open science framework procedure to output data out of an AmpSeq project, with emphasis on the bioinformatics pipeline to generate SNPs, haplotypes and presence/absence variants in a set of diverse genotypes. Open-access tutorial datasets with actual data and a containerization open source software instance are provided to enable training in each of these genotyping applications. The pipelines presented here should be applicable to analysis of various target-enriched (eg, amplicon or sequence capture) Illumina sequence data.